Analysing the Role of Management Skills, Leadership Styles, and Critical Factors in Achieving Successful Project Management Outcomes in Structural Organizations - Sharma, Anshu (Digital Repository of Theses, 2025)
In structure organisations, this research seeks to understand how leadership styles, critical success factors, and management abilities all play a part in producing desirable project management results. Finding out what managers need to know, how leadership and team management styles affect projects, and what variables contribute most to a project's success were the main goals. A qualitative and quantitative approach is used whereby data from the key stakeholders in the form of closed-ended questionnaires is used alongside literature, reportage, and case studies. Convenience sampling helps to make the study convenient and feasible, while quantitative research employs the use of SPSS (Statistical Packages for Social Sciences) to analyses patterns, relations and trends. The findings underscore management competency areas, including communication, analysis and decision-making, and risk management as variables that play a significant role in defining the outcomes of projects. Transformational and collaborative leadership styles were identified as the most effective in motivating teams and improving performance, whereas transactional leadership produced mixed results. Moreover, the identified key success factors, including the involvement of key stakeholders, availability and distribution of resources, and organisational commitment, were found to be crucial in improving project performance. Several studies identified clear communication structures and well-established rules to enhance project efficiency and cooperation. The research concludes that effective project management necessitates attending to several facets of the management process and using best practices in leadership and management. They provide recommendations for enhancing managerial behaviours and communication with and within structured projects as well as advancing the theory of project management by capturing the interaction process of a project environment as depicted by the managerial competencies, leadership styles, and organisational structures.